Étale contractible varieties in positive characteristic - Holschbach, Armin; Schmidt, Johannes; Stix, Jakob (Algebra & number theory, 2014)
Unlike in characteristic 0, there are no nontrivial smooth varieties over an algebraically closed field k of characteristic p>0 that are contractible in the sense of étale homotopy theory.
Gesehen am 06.04.2018